1989
DOI: 10.1159/000199823
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Prognostic Features of Rectal Sparing in Ulcerative Colitis

Abstract: Thirty patients with ulcerative colitis who had been followed clinically for more than 5 years were studied. Patients with total or left-sided colitis were investigated to evaluate the significance of rectal sparing in the prognosis of the disease. Patients were divided into two groups, one with complete or relative sparing of the rectum and the other with homogeneous lesions ranging from the rectum to the proximal colon based on endoscopic findings. The administration of topical corticosteroids seemed to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 6 publications
(12 reference statements)
1
16
0
Order By: Relevance
“…We have previously reported factors in volving the intractability of UC that are of use in the establishment of long-term prog nosis [12]. In addition, the assessment of severity during the acute phase is also of importance in the treatment of patients with UC.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported factors in volving the intractability of UC that are of use in the establishment of long-term prog nosis [12]. In addition, the assessment of severity during the acute phase is also of importance in the treatment of patients with UC.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, however, it has become increasingly evident that patchy colonic involvement, proximal greater than distal disease activity, and frank rectal sparing can occur in treated UC or in UC of many years duration, even in the absence of medical therapy. [2][3][4][5][6][7][8][9] Because initial medical management often is similar for either disease, many clinicians begin therapy for inflammatory bowel disease on the basis of the pathology evident in limited biopsy specimens obtained during flexible sigmoidoscopy. Some time later, when issues of colonoscopic surveillance or possible colectomy are raised or when newer therapies specific to one disease (such as methotrexate, cyclosporine, or infliximab 10 ) are being considered, pathologists are asked to distinguish unequivocally between UC and Crohn colitis, usually on biopsy specimens obtained while the patient is being treated.…”
mentioning
confidence: 99%
“…In these patients, however, rectal biopsies showed changes compatible with ulcerative colitis (three with only mild changes). Oshitani et al reported nine of 30 patients (30%) with ulcerative colitis who had absolute or relative endoscopic rectal sparing; however, no biopsies were taken in this study (11). In 14 patients enrolled in a topical 5-aminosalicylic acid treatment trial, nine patients (64%) were later found to have normal rectal biopsies, although, interestingly, two had been treated with placebo (12).…”
mentioning
confidence: 57%